Nicotinic modulation of network and synaptic transmission in the immature hippocampus investigated with genetically modified mice - Le Magueresse, Corentin (Blackwell Science Inc, 2006)
The hippocampus, a key structure in learning and memory processes, receives a powerful cholinergic innervation from the septum and contains nicotinic acetylcholine receptors (nAChRs). Early in postnatal development, activation of nAChRs by nicotine or endogenous acetylcholine contributes to enhance synaptic signalling. Here, the patch-clamp technique was used to assess the contribution of α7 and β2-containing (α7* and β2*) nAChRs to nicotine-elicited modulation of GABAergic and glutamatergic activity at the network and single-cell level in the immature hippocampus of wild-type (WT), α7−/− and β2−/− mice. We found that α7* and β2* nAChRs were sufficient to modulate nicotine-induced increase in frequency of spontaneously occurring giant depolarizing potentials (GDPs), which are generated at the network level by the synergistic action of glutamate and depolarizing GABA, and thought to play a crucial role in neuronal wiring. However, α7* but not β2* receptors were essential in nicotine-induced increase of interictal discharge frequency recorded after postnatal day 3 in the presence of bicuculline, when GABA shifted from the depolarizing to the hyperpolarizing direction. To correlate these observations with nicotine-elicited changes in synaptic transmission, we recorded spontaneous GABAergic and glutamatergic postsynaptic currents in pyramidal cells and interneurons localized in stratum oriens, stratum pyramidale and stratum radiatum, in slices obtained from WT and knock-out animals. We found that early in postnatal life α7* and β2* nAChRs exert a fine regional modulation of GABAergic and glutamatergic transmission that underlies nicotine-elicited changes in network synchronization.